Simplicity and Authority: Reflections on Theory and Practice in Kant's Moral Philosophy - Timmermann, Jens (Journal of moral philosophy, 2007)
Abstract What is the proper task of Kantian ethical theory? This paper seeks to answer this question with reference to Kant's reply to Christian Garve in Section I of his 1793 essay on Theory and Practice. Kant reasserts the distinctness and natural authority of our consciousness of the moral law. Every mature human being is a moral professional—even philosophers like Garve, if only they forget about their ill-conceived ethical systems and listen to the voice of pure practical reason. Normative theory, Kant argues, cannot be refuted with reference to alleged experience. It is the proper task of the moral philosopher to emphasize this fact. The paper also discusses Kant's attempts to clarify his moral psychology, philosophy of value and conception of the highest good in the course of replying to Garve's challenge.